Its your turn: Enhancing visually induced self motion illusions (“vection”) with walking motions in virtual reality - Freiberg, Jacob; Riecke, Bernhard E. (54th Annual Meeting of the Psychonomic Society (Psychonomics), 2013)
Visual illusions have fascinated humans for centuries, especially embodied illusions such as self-motion illusions ("vection"). Here, we investigate if such visually-induced self-rotation illusions can be enhanced by adding biomechanical cues. To this end, participants sat stationary atop a circular treadmill as they experienced circular vection induced by either visual cues, biomechanical cues, or both. Vection was induced visually using a wide field of view head mounted display showing simulated self-rotations in a naturalistic environment, and/or induced biomechanically from stepping along a carrousel-like rotating floor ("circular treadmill"). While visual and biomechanical cues alone were equally effective in inducing vection, combining them resulted in more intense self-motion illusions and earlier vection onset. The observed cross-modal benefit extends earlier findings for audio-visual and audio-biomechanical vection. Results further guide our development of an affordable yet effective self-motion simulation paradigm for psychological research and virtual reality applications.
Keywords: Riecke; Riecke_2013; bernhard-riecke; iat802; iat802_fall2012; interference; jake-freiberg; multi-modal vection; posterWithoutPaper; proj--vection; spatial; talkWithoutPaper; vection